Performance analysis and pricing efficiency of Exchange Traded Funds(ETFs) during the interest rate hikes: the comparison between equity ETFs and fixed income ETFs in the U.S - Chong, Ken Hung (2020)
Exchange-Traded Funds (ETFs) is a financial instrument whose primary goal is to imitate the performance of the benchmark index while providing investors an efficient way to achieve diversified portfolio. The prices of ETFs are determined by demand and supply rather than net asset value. In order to ensure ETFs to trade at prices approximate to net asset value, the arbitrage mechanism is created to eliminate any mispricing. The largest ETFs by asset class is Equity ETFs followed by Fixed Income ETFs and Commodity ETFs. Over the past ten years, the global ETF industry has recorded tremendous growth from US 300 billion to over 5.1 trillion. The rapid growth of the ETF market is attributed to the benefits of ETFs such as diversification, low management fees, trading flexibility, and tax efficiency.